Knowledge, Attitudes, and Practices on Infection Control Measures in Stomatology Students in Lima, Peru. (12th September 2018) - Silva, Oscar; Palomino, Silvia; Robles, Ada; Ríos, Jorge; Mayta-Tovalino, Frank
Abstract : Introduction . The level of knowledge, attitudes, and practices with respect to infection control measures in undergraduate stomatology students is not well understood; that is why these variables were evaluated in the students of the Universidad Privada San Juan Bautista between September and November of 2017. Methods . A cross-sectional study was carried out. A total of 347 students from the Ica, Lima Norte, and Chorrillos campuses were evaluated. The sample was calculated using the statistical formula of comparison of means. The questionnaire of the CDC (Center of Contagious Diseases) was used to measure the variables described. Results . It was observed that 72.05% of the students preferred to use oral rinsing before starting a treatment, 72.62% used the autoclave as the primary equipment to sterilize their instruments in the dental clinic, 95.10% considered that isolation is important in the control of the infection, 46.40% affirmed that tuberculosis is the most infectious disease, and only 26.51% considered it to be hepatitis B. On the other hand, it was found that the scores of knowledge, attitudes, and practices were 2.74 ± 2.16, 3.59 ± 0.88, and 3.59 ± 1.73, respectively. Conclusions . The level of knowledge was low among the students evaluated; however, as far as the level of practices and attitudes was high, even so, this topic must be reinforced so that stomatology students reflect on the importance of the risks that exist to get infected with any disease inside the dental office, as outside of it.